Regional electricity generation and employment in UK regions. Issue 3 (4th March 2017) - Bryan, Jane; Evans, Neil; Jones, Calvin; Munday, Max
ABSTRACT: Regional electricity generation and employment in UK regions. Regional Studies . A number of electricity-generation technologies reduce carbon emissions, but with different economic and employment effects, partly consequent on how far generation capacity supports regional supply chains. In devolved regions these issues are important because of the role given to renewable electricity generation in economic development strategies. This paper analyses the regional employment supported by different electricity-generation technologies, illustrating trade-offs between generation scale and employment intensity, and shows that the regional employment supported under all pathways is modest compared with the regional economic scale. The policy implications are investigated.